Quality of Life, Life Satisfaction among Elderly People in China Nursing Homes: A Scoping Review - Zhiyou, Yin; Voon, Siok Ping (Asia Pacific Academy of Science Pte. Ltd, 2024)
The problem of population aging in China is becoming increasingly serious, and the demand for old-age care continues to climb. In order to understand the real needs of elderly care services and provide policy references for the development of community care services, this review explored the quality of life, life satisfaction, loneliness, and quality of care experienced by elderly residents in nursing homes in China. Utilizing a mixed-methods approach, the study collected data from nursing homes in four cities: Xi'an, Urumqi, Jinan, and Zibo. The findings highlight significant variations in residents' experiences and provide recommendations for improving their well-being. The results show that the elderly in China's nursing homes are satisfied, and they hope that nursing homes can carry out more activities and provide personalized diets. It is suggested that human culture management mechanisms and effective communication mechanisms can be adapted to meet the individual needs of the elderly residents in community nursing homes, and the whole society can participate in meeting the social needs of the elderly residents in community nursing homes, which will be conducive to improving the happiness of life of the elderly.